Assessing the effectiveness of drought anticipatory action in Uganda's agro-pastoral drylands: A cost-benefit analysis - Mukwaya, Puff Ray (Jameel Observatory for Food Security Early Action, 2025)
Presented at the Jameel Observatory Community of Practice meeting and drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 13-16 May 2025